Exposure to a "safe" dose of environmental pollutant bisphenol A elevates oxidative stress and modulates vasoactive system in hypertensive rats. (December 2021) - Nagarajan, Manigandan; Raja, Boobalan; Manivannan, Jeganathan
Due to the prevalence of hypertension (one of the major risk factors of CVD) in the population, it is necessary to explore the adverse effects of daily tolerable and "safe" dose of bisphenol A (BPA) under hypertensive conditions. The current study exposed the Nω-nitro-l-arginine methyl ester (L-NAME, 40 mg/kg b.w/day) induced hypertensive Wistar rats to BPA (50 μg/kg b.w/day) by oral administration along with appropriate controls for 30 days period. The results illustrate that a 'safe' dose of BPA does not influence the systolic blood pressure (SBP) and levels of circulatory biomarkers of tissue damage. On the other hand, BPA exposure significantly ( p < 0.05) elevates the thiobarbituric acid reactive substances (TBARS) content in plasma and tissues (heart, aorta, liver and kidney) in hypertensive rats when compared with respective control (BPA alone exposed) rats. Similarly, a significant modulation of ROS generation in RBC, plasma nitric oxide (NO) level and angiotensin-converting enzyme (ACE) activity was observed only under hypertensive milieu. In conclusion, the observed adverse effects during 'safe' dose of BPA exposure are specific to the hypertensive condition. Therefore, a precise investigation to explore the effects of BPA exposure in vulnerable hypertensive populations is highly suggested.